Rationale and design of a randomized trial to test the safety and non-inferiority of canagliflozin in patients with diabetes with chronic heart failure: the CANDLE trial. Issue 1 (December 2016) - Tanaka, Atsushi; Inoue, Teruo; Kitakaze, Masafumi; Oyama, Jun-ichi; Sata, Masataka; Taguchi, Isao; Shimizu, Wataru; Watada, Hirotaka; Tomiyama, Hirofumi; Ako, Junya; Sakata, Yasushi; Anzai, Toshihisa; et al.
Abstract Background Because type 2 diabetes mellitus is associated strongly with an increased risk of cardiovascular diseases, the number of patients with diabetes with chronic heart failure is increasing steadily. However, clinical evidence of therapeutic strategies in such patients is still lacking. A recent randomized, placebo-controlled trial in patients with type 2 diabetes with high cardiovascular risk demonstrated that the SGLT2 inhibitor, empagliflozin, reduced the incidence of hospitalization for heart failure. Because SGLT2 inhibitors cause a reduction in body weight and blood pressure in addition to improving glycemic control, they have the potential to exert beneficial effects on the clinical pathophysiology of heart failure. The aim of the ongoing CANDLE trial is to test the safety and non-inferiority of canagliflozin, another SGLT2 inhibitor, compared with glimepiride, a sulfonylurea agent, in patients with type 2 diabetes mellitus and chronic heart failure. Methods A total of 250 patients with type 2 diabetes who are drug-naïve or taking any anti-diabetic agents and suffering from chronic heart failure with a New York Heart Association classification I to III will be randomized centrally into either canagliflozin or glimepiride groups (1: 1) using the dynamic allocation method stratified by age (<65,  ≥65 year), HbA1c level (<6.5,  ≥6.5 %), and left ventricular ejection fraction (<40,  ≥40 %). After randomization, all the participants will be given the add-on study drug for 24 weeks in addition to their background therapy. The primary endpoint is the percentage change from baseline in NT-proBNP after 24 weeks of treatment. The key secondary endpoints after 24 weeks of treatment are the change from baseline in glycemic control, blood pressure, body weight, lipid profile, quality of life score related to heart failure, and cardiac and renal function. Discussion The CANDLE trial is the first to assess the safety and non-inferiority of canagliflozin in comparison with glimepiride in patients with type 2 diabetes with chronic heart failure. This trial has the potential to evaluate the clinical safety and efficacy of canagliflozin on heart failure. Trial registration Unique trial Number, UMIN000017669